Single‐dose versus low‐dose rituximab in corticosteroid‐resistant or relapsed ITP: A multicenter, randomized, controlled study. Issue 4 (25th January 2022) - Ni, Xiaofei; Li, Daqi; Yuan, Chenglu; Yu, Yafei; Wang, Haoyi; Wang, Lingjun; Yu, Tianshu; Qin, Ping; Peng, Jun; Hou, Ming; Shi, Yan; Hou, Yu
Abstract: Primary immune thrombocytopenia (ITP) is an autoimmune bleeding disorder, in which rituximab (RTX) induces the best long‐term effect among recommended second‐line treatments. Nevertheless, the optimal regimen of RTX remains unclear. We herein conducted a prospective, multicenter, open‐label, randomized controlled trial to compare the efficacy and safety of RTX at two different dosage regimens in patients with corticosteroid‐resistant or relapsed ITP. Recruited patients were randomly assigned (1:1) to receive either RTX at a repeated low dose (100 mg weekly for 4 weeks, LD‐RTX) or at a single dose (375 mg/m 2, S‐RTX). Overall response was achieved in 64.3% of patients who received LD‐RTX versus 67.4% of those receiving S‐RTX ( p  = .759). The complete response (CR) rate was 23.8% after LD‐RTX and 28.3% after S‐RTX ( p  = .635). In health‐related quality of life, S‐RTX improved patients' psychological status, quality of life, social activities, and work compared with LD‐RTX. Furthermore, S‐RTX significantly reduced physician visits without compromising efficacy. Our findings demonstrate that a S‐RTX is comparable to LD‐RTX in effectiveness and safety for treatment of corticosteroid‐resistant or relapsed ITP. The single‐dosage regimen optimizes the use of medical resources, improves the cost‐effectiveness of RTX, and represents a promising and more convenient replacement for LD‐RTX in ITP. This study has been completed and is registered with ClinicalTrials.gov, number NCT03258866.